An exploratory case study on the wellbeing of nurses working in a casualty unit at a state hospital in Windhoek - Nyambe, Namukolo (My University, 2020)
Nursing is a profession within the health care sector focused on the care of individuals, families and communities so they may attain and maintain optimal health and quality of life. Psychological wellbeing is an essential aspect for nurses, as the psychological wellbeing of nursing staff may affect patient care in one way or another. Namibia is faced with a human resource crisis in the public health sector. In this research study the researcher focused on exploring the wellbeing of nursing staff in a local public hospital in Windhoek, Namibia. Hertzberg’s motivational theory was the theoretical framework which guided this study. A qualitative exploratory multiple case study research design was employed and data were collected with a semi-structured interview schedule using face-to-face interviews. A total of ten nurses were selected to participate in the study using purposive sampling. Qualitative data gathered were analysed using thematic analysis. The study found that a shortage of staff at Casualty Unity was the main challenge experienced by the nurses working at the unit under review and that this in turn negatively affects their wellbeing. A shortage of registered nurses at a local public hospital in Windhoek impacts on their psychological wellbeing which consequently negatively affects patient care and service delivery. Findings showed that nurses felt stressed and burned out as a result of their work. Therefore, it is recommended that the hospital management should establish effective stress management strategies to mitigate the challenges faced by the nurses and hence improve the overall wellbeing of nurses
A report on a research study presented to The Department of Social Work, School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Arts in Social Work in the field of Occupational Social Work, 2020